PFOS facilitates liver inflammation and steatosis: An involvement of NLRP3 inflammasome‐mediated hepatocyte pyroptosis. Issue 5 (23rd October 2021) - Qin, Yi; Gu, Tianye; Ling, Junyi; Luo, Jiashan; Zhao, Jianya; Hu, Baoying; Hua, Lu; Wan, Chunhua; Jiang, Shengyang
Abstract: Perfluorooctane sulfonate (PFOS) is a fluorinated organic pollutant with substantial accumulation in mammalian liver tissues. However, the impact of chronic PFOS exposure on liver disease progression and the underlying molecular mechanisms remain elusive. Herein, we for the first time revealed that micromolar range of PFOS exposure initiates the activation of NLR pyrin domain containing 3 (NLRP3) inflammasome to drive hepatocyte pyroptosis. We showed that 5 mg/kg/day PFOS exposure may exacerbated liver inflammation and steatosis in high‐fat diet (HFD)‐fed mice with concurrently elevated expression of NLRP3 and caspase‐1. PFOS exposure resulted in viability impairment and LDH release in BRL‐3A rat liver cells. 25–100 μM concentrations of PFOS exposure activated the NLRP3 inflammasome, leading to consequent GSDMD cleavage, IL‐1β release and the initiation of pyroptosis in a dose‐dependent manner, whereas treatment with 10 μM NLRP3 inhibitor MCC950 abrogated this effect. Moreover, pretreatment of 5 mM ROS scavenger N ‐acetyl‐L‐cysteine (NAC) ameliorated PFOS‐induced NLRP3 inflammasome activation and pyroptosis. Collectively, our data highlight a pivotal role of pyroptotic death in PFOS‐mediated liver inflammation and metabolic disorder. Abstract : Perfluorooctane sulfonate (PFOS) is strongly accumulated in the liver following chronic exposure and may facilitate the progression of liver diseases. This study found that PFOS exposure may promote the activation of NLR pyrin domain containing 3 (NLRP3) inflammasome to drive hepatocyte pyroptosis. Through activating NLRP3 inflammasome, PFOS induces the release of pro‐inflammatory cytokines and may facilitate steatosis in a high‐fat diet (HFD) mouse model. Our findings indicate a prosteatotic effect of PFOS via NLRP3 inflammasome activation and pyroptosis.